Does the Quality of Antenatal Care Predict Health Facility Delivery Among Women in Kenya? Further Analysis of KDHS Data 2008/09 - Obago, Irene T.; Ouma, James O.; Owino, Joyce A. (International Journal of Child Health and Nutrition, 2013)
Improving maternal health remains a priority in Kenya and beyond. It is essential that women get good medical care before, during and after pregnancy to reduce maternal mortality. Skilled delivery care remains low in Kenya and maternal mortality rate high regardless of numerous ongoing interventions. Antenatal care is known to promote maternal and fetal well-being. However less than 50% of women make the recommended four or more antenatal care visits, missing out on key services such as urine and blood tests, and advice on possible pregnancy complications, that determine the quality of ANC. This study examines how the number of ANC visits and the quality of those visits predict health facility use at delivery. Maternal health data from DHS of 2008/2008 in Kenya was analyzed using Stata 11.0 software. Logistic regression was used to evaluate relationships between facility delivery and predictor variables in univariate and multivariate models. Estimates were based on 95% confidence inteval. The models were examined at 95% CI and 80% power and adjusted for maternal age at last birth, education, place and type of residence, level of exposure to media, mother’s religion, wealth index and birth order. The quality of ANC was an index developed based on the number of services received during ANC visits.The quality of ANC visits progressively increased the likelyhood of health facility delivery. Supply and demand should be intervention targets to ensure that women know and understand the services to demand. Health facilities should also be sufficiently prepared and ready with the services.